Nanoscale insight into the p‐n junction of alkali‐incorporated Cu(In, Ga)Se2 solar cells. (5th April 2017) - Stokes, Adam; Al‐Jassim, Mowafak; Norman, Andrew; Diercks, David; Gorman, Brian
Abstract: The effects of alkali diffusion and post‐deposition treatment in three‐stage processed Cu(In, Ga)Se2 solar cells are examined by using atom probe tomography and electrical property measurements. Cells, for which the substrate was treated at 650°C to induce alkali diffusion from the substrate prior to absorber deposition, exhibited high open‐circuit voltage (758 mV) and efficiency (18.2%) and also exhibited a 50 to 100‐nm‐thick ordered vacancy compound layer at the metallurgical junction. Surprisingly, these high‐temperature samples exhibited higher concentrations of K at the junction (1.8 at.%) than post‐deposition treatment samples (0.4 at.%). A model that uses Ga/(Ga + In) and Cu/(Ga + In) profiles to predict bandgaps (±17.9 meV) of 22 Cu(In, Ga)Se2 solar cells reported in literature was discussed and ultimately used to predict band properties at the nanoscale by using atom probe tomography data. The high‐temperature samples exhibited a greater drop in the valence band maximum (200 meV) due to a lower Cu/(Ga + In) ratio than the post‐deposition treatment samples. There was an anticorrelation of K concentrations and Cu/(Ga + In) ratios for all samples, regardless of processing conditions. Changes in elemental profiles at the active junctions correlate well with the electrical behaviour of these devices. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Eight atom probe specimens were presented and gave a never‐seen‐before statistical representation of the variable chemistries at the p‐n junction at small length scales of alkali‐incorporated Cu(In, Ga)Se2 solar cells. A model to relate chemistry to band profiles such as the shifts in conduction band minimum, valence band maximum, and bandgap is also presented.